Phylogenetic position of the crustose Stereocaulon species. (9th January 2014) - HÖGNABBA, Filip; PINO-BODAS, Raquel; NORDIN, Anders; MYLLYS, Leena; STENROOS, Soili
Abstract Phylogenetic relationships of Stereocaulon with emphasis on the crustose taxa were studied based on nuclear ribosomal ITS1–5.8S–ITS2 and partial beta-tubulin sequences. The placement of four of the six crustose species currently included in the genus has previously been confirmed based on molecular data. It has, however, remained unresolved whether the crustose growth form is a plesiomorphic or apomorphic feature within Stereocaulon, due to contradictory placements of the crustose species in earlier studies. The aim of this study was to clarify the position of the crustose species by including additional data, especially of S. nivale and S. plicatile, which have not been included in previous analyses. The inclusion of S. plicatile in the genus is of particular interest as it is the only species in the genus with submurifrom to muriform ascospores. Altogether 37 specimens representing 31 species of the ingroup, including all the crustose Stereocaulon species, were incorporated in the analyses. Conventional, as well as direct optimization parsimony, maximum likelihood and Bayesian analyses were performed. The results show that the crustose species do not form a monophyletic entity and that the crustose growth form is a plesiomorphic feature within Stereocaulon. The crustose S. nivale and S. plicatile are nested within the genus and their inclusion in Stereocaulon is thereby confirmed. The nested position of S. plicatile indicates that the submuriform to muriform spore type has been gained independently within the genus. Here, S. plicatile is also reported for the first time from Scandinavia.